Letter from James F. Daniels - James F. Daniels:::::: (1973)
A letter to the Mayor of Oxnard from James F. Daniels, the chairman of the Port Hueneme Harbor Days Parade, inviting the Mayor and their wife to be guests on the reviewing stand.